2013
DOI: 10.1016/s1995-7645(12)60207-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Bell's palsy – An unusual presentation of dengue infection

Abstract: Dengue fever is a very common arthropod - borne infection in tropical countries. Neurological complications in dengue fever are relatively uncommon and among these, isolated cranial neuropathies have been reported only very rarely. We present an unusual neurological complication of Bell's palsy (lower motor neuron 7 th nerve palsy) associated with dengue infection. To the best of our knowledge, there have been very few documented cases of Flavivirus causing isolated Bell's palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Neurological involvement in dengue may occur because of neurotropism of the virus, immunological mechanisms, cerebral anoxia, intracranial hemorrhage, hyponatremia, cerebral edema, hepatic failure, renal failure, or release of toxic products. Peter et al [16] reported isolated facial nerve palsy in dengue fever and Shivanthan et al [17] have also reported isolated 6th nerve palsy. Donnio et al [18] reported dengue with a rare presentation of oculomotor nerve palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological involvement in dengue may occur because of neurotropism of the virus, immunological mechanisms, cerebral anoxia, intracranial hemorrhage, hyponatremia, cerebral edema, hepatic failure, renal failure, or release of toxic products. Peter et al [16] reported isolated facial nerve palsy in dengue fever and Shivanthan et al [17] have also reported isolated 6th nerve palsy. Donnio et al [18] reported dengue with a rare presentation of oculomotor nerve palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Headache, alteration of consciousness, irritability, insomnia, seizures and focal neurological deficit associated with encephalitis, encephalopathy and stro ke pictures are the most common symptoms observed during the acute dengue. Other neurological manifestations, such as motor deficit can occur in acute dengue infection in cases of myelitis and myositis, or during post-dengue stage, in patients with polyradiculoneuritis, encephalomyelitis, neuromyelitis optica, polyneuropathy and mononeuropathy 8 .…”
Section: Dengue and The Nervous Systemmentioning
confidence: 99%
“…Bell's palsy results in weakness of facial muscles. 8 Bell's palsy, i.e. lower motor neuron seventh nerve palsy has been reported following dengue infection.…”
Section: Discussionmentioning
confidence: 99%
“…lower motor neuron seventh nerve palsy has been reported following dengue infection. 8 , Campylobacter enteritis. 9 , Rickettsial infection.…”
Section: Discussionmentioning
confidence: 99%